Neutrosophic Prevalence Field and Multipolar Dominance: A New Mathematical Model for Decision-Making in Mobile Robot Operational Efficiency Based on Industrial Internet - Dingqun Zhang (Neutrosophic Sets and Systems)
Mobile robots in industrial environments must make fast and accurate decisions, even when data is incomplete, uncertain, or contradictory. This paper introduces a new mathematical model that combines two original ideas: the Neutrosophic Prevalence Field (NPF) and Multipolar Neutrosophic Dominance. The model allows a robot to evaluate possible actions based on truth, uncertainty, and falsehood levels, while also considering how strong or dominant each action is. It also accounts for different goals or influences (called "poles") that may compete during decision-making. We define all components mathematically, present the full decision equation, and explain how the model can help robots make better decisions in complex industrial systems. Several numerical examples are included to show how the method works in practice.